Efeito espasmolídico do Óleo essencial de Lippia Sidoides e do Carvacrol no músculo liso de fundo de estômago de rato: investigação da participação dos canais de cálcio operados por voltagens - Silva, Francisco Rafael Oliveira da (2019)
Lippia sidoides is a medicinal plant of the family Verbenaceae with diverse pharmacological activities among them antispasmodic. Many species of the family Verbenaceae demonstrate in their composition essential oils, endowed with biological activities, thus arousing great pharmacological interest because they present activity on the smooth musculature. Based on these premises, the objective of this work was to investigate the spasmolytic effect of essential oil (OEL) of Lippia sidoides and carvacrol on the smooth muscle of the stomach of the rat. The records were obtained from isolated strips of stomach in preparations for isolated organs through a data acquisition system. Cumulative OEL concentrations (1-300 μg / ml) were added to the bottom of the rat stomach under the effect of the carbachol (CCh) and potassium chloride (KCl) contractors. In the pre-contracted stomach with 60 mM KCl, the shrinkage was reduced to 50% (36.82146 ± 7.9157), 80% (20.83054 ± 7.32411) and 100% (-10.95499 ± 7.73396) at the concentrations of 30, 100 and 300 μg / ml (p <0.05). In the stomach pre-contracted with carbachol and incubated with OEL, the 300 μg / ml dose reduced contraction by 100% (-45.83 ± 40.33). From the findings, Ca2 + -free tissues were preincubated with OEL (1-300ug / mL) and then contracted by cumulative CaCl2 curves (0.1-0.5M - 1-2M) and we found that OEL (100-300 μg / ml) was able to inhibit the contraction curve by almost 90% compared to the control group. In the experiments performed with carvacrol, cumulative concentrations in the proportion of (10-1000 μM) were added to the bottom of the rat stomach under the effect of the CCh and KCl contractors, with the antispasmolytic effect of carvacrol being observed. It was observed that this compound was effective in relaxing pre-contracted tissue with carbachol (CCh) in the proportion of 22%, 35% and 46% in the concentrations 300, 600 and 1000 μM. In the experiment performed with 60 mM KCl, the contractions were reduced in the proportions of 26%, 33%, 42%, 56%, and 70% in the concentrations 30, 100, 300, 600 and 1000 μM. At the concentration of 1000 μM carvacrol in medium at cumulative concentrations of Ca 2+ in 0 Ca 2+ solution, the concentration 0.5 mM inhibited contraction in 61% (11.75 ± 112). However, at 1 mM concentration we had a reduction in contraction of 86% (35.92 ± 136.2) and already the 2mM concentration inhibited the contraction in 71% (21.12 ± 121.4 μg / ml). Carvacrol relaxed 29% of the CCh-induced contraction in the presence of nifedipine. In the protocol with TEA, it was possible to observe that carvacrol in the concentration 1000μM was able to induce relaxation about 14% (-85,23 ± 6,755) in the contraction maintained by CCh. It was found that the essential oil of Lippia sidoides and carvacrol demonstrate antispasmolytic effect involving voltage-operated calcium channel block. In the study of molecular anchoring it was possible to verify that carvacrol occupied a site of attachment far from the pore for the entry of calcium, and it may be suggested that carvacrol may induce a closure in the directed site canal. In addition, the binding energies of carvacrol were negative -6.7 kcal / mol, ranging from -6.1 to -7.0 kcal / mol among nine different conformations, with inhibition constants between 7 ÂμM and 33 ÂμM.